Experience as a Subject of Market Exchange – Theoretical and Methodological Reflections Based on Sports Tourism - Szczechowicz, Bartosz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The paper examines whether approaches and methods developed in economics can be effective in recognising consumer assessments of experience-based products that provide intense and memorable impressions. It assesses the theoretical foundations of product evaluation and their methodological consequences, formulated within mainstream economics (neoclassical economics) and beyond (behavioural economics, experimental economics). Sports tourism was used to exemplify the difficulties that arose in choosing this path to examine the issue. It was found that while mainstream economics can form the theoretical and methodological basis of empirical research on the issue of consumer perception of experience-based products, schools of heterodox economics can provide a greater increase in knowledge in this field.